Customer Relationship Management in Selected Public and Private Tertiary Hospitals of Dhaka City (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Customer relationship management (CRM) is a strategy that helps organizations to build long-term relationship with customer and increase profit through a proper management system.Objective: To understand the present state of CRM in tertiary level public and private hospitals in Dhaka City, by identifying customers’ profile, customers’ expectation, and by assessing customers’ satisfaction.Material and Methods: This cross sectional descriptive study was conducted in two tertiary level hospitals of Dhaka city, from July 2018 to June 2019 among 220 samples from each hospital, by convenience sampling. Data were collected by interview using semi structured questionnaire and reviewing of check list.Results: Among service receivers, high monthly income (>30000 Taka) prefer Uttara Adhunic Medical College Hospital (UAMCH) (23%) than Dhaka Medical College hospital (DMCH) (5%). Doctors explained health condition to patient or relatives in 64% cases in DMCH and 82% cases in UAMCH. Nurses attention for privacy and courtesy towards patient was 75% and 31% in DMCH which was 86.4% and 50% in UAMCH. About 59% and 20% service receivers from public and private hospital respectively were of the view that pharmacy staffs did not explained properly about safe methods of taking drugs. The overall patient satisfaction was found 63.7% and 69.4% in DMCH & UAMCH by using The Patient Satisfaction Questionnaire Short Form (PSQ- 18 scale).Conclusion: All these findings suggest that people are satisfied more with service quality of private hospitals than the public hospitals. Private hospitals trying to fulfill the requirements of the patients according to their service quality demand, in contrast, public hospitals are fighting hard to fulfill patients demand with limited resources.JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 61-64